Աղբյուրագիտական երկու հետազոտություն Ղարաբաղի մասին - Է. Հ. Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
Вопросы истории Карабаха (Арцаха) остаются одними из приоритетных в армянской историографии. Не секрет, что наши коллеги из соседней республики пытаются всячески приукрасить магометанское правление в Карабахе, представляя его как яркую страницу в истории Карабаха. Однако одни лишь архивные документы, изданные в Актах Кавказской археографической комиссии (АКАК), уже доказывают обратное. The problems of the history of Karabakh (Artsakh) remain one of the priorities in Armenian historiography. It's no secret that our colleagues from the neighboring republic are trying every way to embellish the mohammedan rule in Karabakh, presenting it as a flourishing era in the history of Karabakh. However, the archival documents published in the Acts of the Caucasian Archaeographic Commission (ACAC) are more than enough to prove the opposite.
Keywords: History; Auxiliary Sciences of History; Economic History and Conditions; CC Archaeology; D History; H Social Sciences